Sorption and desorption of Suflafenacil in two soils in the state of São Paulo with different physical and chemical attributes - Matallo,M.B. (2014)
A study was conducted to evaluate the sorption and desorption of 14C herbicide saflufenacil (pyrimidinedione) in two soils in the State of São Paulo, classified as Red Yellow Latosol with clayey texture (LVA-1) and medium texture (LVA-2), using the batch method through isotherms. The soils were air dried and sieved a 2 mm mesh. The radioactivity was determined by liquid scintillation spectrometry in acclimatized room (25 ± 2 °C). Sorption isotherms were conducted for 5 concentrations of saflufenacil (5.0; 2.5; 1.0; 0.5 and 0.05 μg mL-1) and the results were adjusted to the Freundlich equation, thus obtaining the parameters of sorption followed by two extractions with 0.01 M CaCl2 to determine desorption parameters similarly to sorption. The results showed that saflufenacil sorption was low for both soils studied, being greater for the LVA with higher organic matter content. The desorption coefficients were greater than their sorption coefficients, suggesting the occurrence of hysteresis. The sorption and desorption isotherms (classified as type C isotherms), hysteresis and the t-test between the angular coefficient of the respective isotherms showed that both the sorption and desorption occur with equal intensity.